Effectiveness of behavioral modification intervention to reduce cardiovascular disease risk factors among public secondary school students in Brong Ahafo, Ghana - Amoah, John (2019)
Globally, cardiovascular disease (CVD) was responsible for 17.5 million deaths, accounting for 46.2% of non-communicable diseases (NCDs) deaths. In Ghana CVDs has been the leading cause of death since 2001. The prevalence of CVD risk factors among adolescents and adults in Ghana has been increasing. The main aim of this study were to develop, implement and evaluate the effectiveness of a behavioral modification intervention program to reduce cardiovascular disease risk factors among secondary school students in Brong Ahafo, Ghana. The study was a single blind cluster randomized controlled trial. Baseline data was collected from 848 students after which schools were evenly randomized using block randomization (1:1 ratio) of two digit blocks (A and B). School-based intervention was implemented using the InformationMotivation-Behavioral skills (IMB) model to reduce CVD risk factors over a period of six months with pre and post intervention evaluations. The intervention module included a health education and physical activity modules in the intervention schools. The control schools went on with their normal school curriculum and were waitlisted for similar intervention after the study. Follow-up data using same questionnaire were collected within two weeks after the intervention was completed. The primary outcomes were knowledge, motivation, behavioral skills, physical activity, smoking, alcohol, dietary intake, while weight, body mass index, and blood pressure were secondary outcomes. Weight, height and blood pressure were measured using standardized equipments by trained health staff. Intention-to-treat analysis was performed after replacing missing values using multiple imputation method. The generalized linear mixed model (GLMM) was used to test the effect of group, time and group-time interactions after controlling for nine potential confounders. The GLMM analyses showed the intervention was significant in attaining 6.85(p<0.001), 0.90(p<0.001), 0.94(p<0.001), 0.77(p<0.001), 0.72(p<0.001), 0.47(p<0.001), 0.56(p<0.001), and 0.39(p=0.045) higher total knowledge, motivation, behavioral skills, physical activity, fruits, vegetables, seafood, and water scores respectively for the intervention group over the control group. The intervention was also significant in reducing -0.15(p<0.001), -0.23(p<0.001), -0.50(p<0.001), -0.32(p<0.001), - 0.90(p<0.001), -0.87(p<0.001),-0.38(p<0.001),-0.63(p<0.001), -1.63(p<0.001), - 0.61(p<0.001), and -1.53(p=0.005) carbohydrates, fats and oils, fried eggs, fried chicken, carbonated drinks, sugar, sweet snacks, salted fish, weight, BMI, and diastolic BP. The ‘’odds’’ of quitting alcohol use in the intervention group was 1.06 times more than in control group. There was no significant effect for groups on smoking, but group-time interaction was significant (F (1,101) = 5.07, p=0.027) and the odds of quitting smoking in the intervention group was 6.13 times more than the control group (t=2.251, p=0.027). There was no significant effect of the intervention on reducing systolic BP. The intervention had a positive effect on increasing physical activity levels, promoting healthy dietary habits, reducing smoking habits and alcohol consumption, weight, BMI, diastolic BP and improving CVD knowledge, motivation and behavioral skills among students in the intervention arm of the study but had no effect on systolic BP. The findings from this study is recommended to be adopted as part of the educational curricula in secondary schools in Brong Ahafo, Ghana.